COMBINED INSIDE-OUT AND ALL-INSIDE TECHNIQUE IN BUCKET-HANDLE MENISCUS TEARS - Yılmaz,Serdar (2016)
ABSTRACT Objective: To determine the outcomes after combined inside-out and all-inside repair technique of bucket-handle meniscus tears. Methods: A retrospective review was made of patients with bucket-handle meniscus tears repaired with combined techniques, using the all-inside technique in posterior meniscal tears and the inside-out technique in the middle part of the meniscal tears. Meniscal healing was assessed clinically using Barrett's criteria and MRI. Results: The study comprised 52 patients with a mean age of 28.4 years old (range, 19-52 years old). The mean follow-up period was 31.3 months (range, 24-59 months). Two patients had ACL re-rupture, and complete meniscal healing was achieved in all but one patient. Although improved from preoperative status, Tegner and Lysholm scores were lower in the ACL reconstructed patients than in the intact ACL patients. Conclusion: Combined inside-out and all-inside meniscal repair technique is a successful and cost-effective treatment method in bucket-handle meniscus tears. Level of Evidence IV, Therapeutic Study.